2023
DOI: 10.1186/s12885-023-10947-7
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 stimulation can promote proliferation and survival of leukemic cells by influencing glucose and fatty acid metabolism in acute myeloid leukemia

Abstract: Background Leukemic cell metabolism plays significant roles in their proliferation and survival. These metabolic adaptations are under regulation by different factors. Programmed Death Ligand -1 (CD-274) is one of the immune checkpoint ligands that do not only cause the immune escape of cancer cells, but also have some intracellular effects in these cells. PD-L1 is overexpressed on leukemic stem cells and relates with poor prognosis of AML. In this study, we investigated effects of PD-L1 stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Furthermore, it is associated with cancer stem cell proliferation (Azuma et al 2008 ; Yang et al 2015 ). PD-L1 can enhance the proliferation and survival of acute myeloid leukemia cells by upregulating the pentose phosphate pathway, which is crucial for cell proliferation and the β -oxidation of fatty acids, which promotes cell survival (Soltani et al 2023 ). PD-L1 suppresses tumor autophagy by promoting basal mTORC1 signaling in melanoma and ovarian cancer models (Clark et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is associated with cancer stem cell proliferation (Azuma et al 2008 ; Yang et al 2015 ). PD-L1 can enhance the proliferation and survival of acute myeloid leukemia cells by upregulating the pentose phosphate pathway, which is crucial for cell proliferation and the β -oxidation of fatty acids, which promotes cell survival (Soltani et al 2023 ). PD-L1 suppresses tumor autophagy by promoting basal mTORC1 signaling in melanoma and ovarian cancer models (Clark et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 promoted stem cell proliferation and survival through changes in glucose metabolism and fatty acid metabolism in leukemia cells. 38 In acute myeloid leukemia, PD-L1 activated the PI3K-AKT signaling pathway to regulate cell proliferation and apoptosis. 39 PD-L1 promoted invasion and metastasis in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another option is an in-depth insight into additional pathways that could influence the response of leukemic cells to therapy with anti-PD-L1. Soltani et al suggested that certain metabolic pathways of leukemic cells that were affected by blockers of PD-L1, might be promising targets for novel drugs implemented additionally in ICI therapy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%